Koperasi Desa Merah Putih dengan Pendekatan Usaha Mudharabah: Studi Kasus di Desa Jingkang, Sumedang - Dadan Hamdani (LPPM Universitas Koperasi Indonesia, 2025)
This study examines the implementation of the Mudharabah business approach in the management of Koperasi Desa Merah Putih located in Desa Jingkang, Sumedang. Mudharabah, a profit-sharing partnership where the cooperative acts as the capital provider (shahibul maal) and members as business managers (mudharib), offers an equitable and transparent financing model aligned with Islamic principles. Employing a qualitative descriptive method, data were collected through interviews, observations, and document analysis during the cooperative’s operational activities. The findings reveal that the cooperative successfully applies clear profit-sharing agreements and transparent distribution mechanisms, which enhance member motivation and business development. Challenges such as limited financial literacy on Islamic finance and operational supervision were addressed through regular training and the establishment of a village sharia supervisory board. The study recommends continuous mentoring and digitalization of cooperative administration to ensure the sustainability of the Mudharabah model. Thus, the application of Mudharabah in Koperasi Desa Merah Putih demonstrates significant potential as an inclusive and sustainable community economic empowerment model based on sharia principles.